KONDISI UMKM BATIK DI KABUPATEN SRAGEN PROPINSI JAWA TENGAH - ASRI LAKSMI RIANI; JULIANUS JOHNNY SARUNGU; MARGANA MARGANA (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2015)
The research aims to explore the condition of batik small medium enterprises in Sragen to improve the income and welfare of batik community, support the development of creative industry, and enhance the regional economy. The objectives of this study were: (1) to explore the potentials of batik industry in supporting the development of creative industry based on local wisdom, (2) to identify the opportunities to develop batik industry in Sragen. This research employed descriptive-qualitative approach. Data were collected using several methods including observation and interview. Data analysis techniques applied in this study consisted of interactive analysis (Miles & Huberman, 1984) and internal-external analysis. The results show that the raw materials used mostly by the batik industry are cotton (prima and primisima). Most of the raw materials are from Surakarta. Raw materials are purchased both in cash and credit. The proportion of cash and credit purchase are almost equally the same. Most of the batik small medium enterprises use chemical colouring substances to produce batik. Most of their products are handmade batik (batik tulis), printed batik, stamped batik, and combination between stamped and handmade. Most of the batik are produced manually. Most of the buyers demand cotton batik produced using combination technique and natural colour. Batik of 250 cm size are preferred.